2020
DOI: 10.1186/s13063-020-04756-7
|View full text |Cite
|
Sign up to set email alerts
|

Research transparency promotion by surgical journals publishing randomised controlled trials: a survey

Abstract: Objective To describe surgical journals’ position statements on data-sharing policies (primary objective) and to describe key features of their research transparency promotion. Methods Only “SURGICAL” journals with an impact factor higher than 2 (Web of Science) were eligible for the study. They were included, if there were explicit instructions for clinical trial publication in the official instructions for authors (OIA) or if they had published randomised controlled trial (RCT) between 1 January 2016 and 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Even data on transparency and on data sharing practices or the promotion of data sharing in the surgical community are scarce. 7 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even data on transparency and on data sharing practices or the promotion of data sharing in the surgical community are scarce. 7 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with a growing literature demonstrating that the ICMJE data sharing policy has not yet succeeded in making data available from RCTs. Even data on transparency and on data sharing practices or the promotion of data sharing in the surgical community are scarce …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research transparency promotion, such as through data-sharing policies, is quite limited in surgical journals. [20][21][22] Therefore, many surgical studies, specifically concerning RCTs, have not been reproducible. 23 These results could allude to the fact that implementing open science practices in surgical research could be quite difficult due to unique challenges.…”
Section: Neurosurgicalmentioning
confidence: 99%
“…Similarly, a systematic review of studies in pediatric surgery published in 1998 and 2013 found that only 1.8% and 1.9%, respectively, were RCTs [2]. These figures are even poorer than those for adult surgery: a review of 87 surgical journals by Lombard et al (2020) found that only 18% of surgical journals had published an RCT between 2016 and 2018 [3]. This is a long‐standing trend.…”
Section: Introductionmentioning
confidence: 99%